Factors Affecting Generation Z’s Interest In Cryptocurrency Investment In Bengkulu City - Shendi Putra Alpino; M Rahman Febliansa; Yun Fitriano (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the factors affecting Generation Z’s interest in investing in cryptocurrency in Bengkulu City. The factors examined in this study include financial literacy, profit motivation, and risk perception. This research uses a quantitative approach with an associative method. The sample consists of 120 Generation Z respondents aged 18–28 years who have an interest or experience in cryptocurrency investment. Data were collected through questionnaires distributed online using Google Forms and measured using a Likert scale. The data were analyzed using multiple linear regression analysis with the assistance of SPSS software, including validity tests, reliability tests, classical assumption tests, t-tests, F-tests, and coefficient of determination (R²). The results of the study show that financial literacy, profit motivation, and risk perception have a positive and significant effect on Generation Z’s interest in cryptocurrency investment, both partially and simultaneously. The coefficient of determination indicates that a substantial proportion of the variation in investment interest can be explained by these three variables, while the remaining variation is influenced by other factors not examined in this study. These findings indicate that higher financial literacy, stronger profit motivation, and appropriate risk perception can increase Generation Z’s interest in cryptocurrency investment. Therefore, improving financial literacy and risk awareness among Generation Z is important to encourage more rational and responsible investment decisions.